Properties of organic compounds on CD- ROM (Chapman & Hall/ CRC, 2000)
Properties of Organic Compounds on CD-ROM contains more than 29,000 of the most commonly sought organic compounds, featuring physical data, spectral data, and structures. With a high-quality display, powerful search capabilities, high-resolution output, and superior help utility, this relational database acts as an easy-to-use tool for identifying unknown compounds or for locating additional data and references for a known compound. Let Properties of Organic Compounds on CD-ROM save you time and money... in the library...in the laboratory...in the classroom!